Reconstruction of the abdominal wall with component separation technique in patients with giant omphalocele - C. Lagos Jefferson; C. Torres; F. Anich; M. Obaíd; A. Paulos; V. Broussain; S. Montedónico; P. Quijada (Journal of Pediatric Surgery Open, 2024)
Background: Several techniques have been described to repair giant omphaloceles. Component Separation Technique (CST) is a surgical technique first reported in adults to repair large abdominal wall defects. The purpose of this study is to describe our experience using this technique in repairing large ventral hernias secondary to giant omphaloceles in children. Methods: Nine patients with giant omphalocele were treated. The abdominal wall was reconstructed using CST, based on the enlargement of the abdominal wall by separate mobilization of the muscular layers. Patients were monitored for complications during admission, postoperative complications, and all patients were seen for follow-up. Results: Component separation technique was performed at a median age of 7.2 years. The median diameter of the hernia was 109.8 cm2. There was no mortality. Minor complications were seen (infection, skin necrosis, and hematoma). There were no recurrences after an average follow-up of 3.3 years (2 - 4 years). Conclusions: Component separation technique is a valuable method for repairing large ventral hernias as a consequence of giant omphaloceles in children. Our series supports the use of CST in children, in a wide age range, from newborns for primary closure to adolescence in cases of giant ventral hernias secondary to omphaloceles with multiple previous surgeries. Level of Evidence: II